2022
DOI: 10.1186/s12909-021-03074-z
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of graduates of rural oriented medical students training project in Jiangsu Province, China: a cross-sectional study

Abstract: Background The Chinese government has worked out the “Rural Oriented Medical Students Training Project” to address physician maldistribution, which attempted to train physicians for rural areas. The present study attempted to evaluate the job satisfaction of the graduates of this project in Jiangsu Province, China. Methods Online questionnaires were sent to the graduates of the “Rural Oriented Medical Students Training Project” (group A) and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…Consistent with similar works we found a positive relationship between financial incentives and medical students’ job choices [ 30 , 31 ]. However, with the upward trend in the monthly income, the results showed that jobs with same non-financial attributes consistently had higher utility, which demonstrated financial incentives were not as the most effective interventions underlying job preferences as previously believed.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with similar works we found a positive relationship between financial incentives and medical students’ job choices [ 30 , 31 ]. However, with the upward trend in the monthly income, the results showed that jobs with same non-financial attributes consistently had higher utility, which demonstrated financial incentives were not as the most effective interventions underlying job preferences as previously believed.…”
Section: Discussionsupporting
confidence: 92%
“…Students under this policy are required to complete five years of medical education, followed by three years of standardized training, and then serve for three years at township health clinics. As identified in existing research, a significant number of these medical students report low job satisfaction [ 20 , 21 ] with a pronounced intention to resign [ 22 ]. The principal reasons cited for this discontent are the low levels of pay, long working hours, scarce opportunities for further training, and limited prospects for career advancement.…”
Section: Discussionmentioning
confidence: 99%
“…The increased workload extended GPs’ working hours and might further reduce their income from other part-time jobs [ 52 , 53 ]. Therefore, in order to retain GPs in rural area, the provision of appropriate financial support such as stipends and subsidies should be taken into account [ 24 , 54 ]. In particular, the access to and a secure of retirement pension has been found to be an important incentive for health professionals to practice in rural settings [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been a large body of investigations on turnover intention and job satisfaction among primary health workforce in rural China [20,[24][25][26], there is a research gap regarding GPs' perceptions towards NCSP and its potential impact on their turnover intention in rural area. Given the unique role of NCSP GPs, it is necessary to investigate their perceptions towards such policies as the restriction on taking postgraduate exam [16].…”
Section: Introductionmentioning
confidence: 99%